The Roman Curia: history, theology, and organization - Ekpo, Anthony (Georgetown University Press, 2024)
"The Roman Curia is the central body for the administration of the Roman Catholic Church. The structure and organization of the Curia are governed by Praedicate evangelium, issued by Pope Francis in 2022. The Curia is both difficult to understand and vitally important for the administration of the Church and the Vatican. Interest in the Curia has been growing since Francis' 2022 reform, and this book provides a historical, theological, and juridical explanation of the nature of the Roman Curia, highlighting its relationship to the Pope. It is intended as an overview of the Roman Curia and allied ecclesiastical institutions, like the Vatican and the Holy See, for those unfamiliar with their nature and operation. The book is divided into seven chapters. Chapter one explains the three terms that are often used interchangeably but refer to different entities: The Vatican City State, the Holy See and the Roman Curia. While chapter two offers a brief history of the Curia, chapter three focuses on the concrete steps that led to the production of PE, the principles and criteria that inspired it, the meaning of its title and its noteworthy innovations. Chapter four treats the theological self-understanding that underpins the Roman Curia as developed in PE. Chapter five concentrates on the Secretariat of State and the sixteen Dicasteries of the Roman Curia, offering a brief history and an examination of the juridical structures and responsibilities of each. In a similar way, Chapter six offers a brief historical note and reflection on the juridical competence of each of the institutions of justice of the Roman Curia. So too, Chapter seven reflects on the history and internal juridical ordering of the institutions of finance and other Offices of the Roman Curia"--